Effect of excimer laser annealing on the silicon nanocrystals embedded in silicon-rich silicon nitride film - Chen, Rui (2013)
The investigations of silicon-rich silicon nitride film grown by plasma-enhanced chemical vapor deposition and then annealed by excimer laser have been carried out systematically. The surface roughness and the crystallization of the films have significantly been improved after the excimer laser annealing. The samples demonstrate visible photoluminescence emission under optical excitation at room temperature. It is found that the emission peak energy as well as emission intensity changes with laser annealing conditions, and the relevant mechanism is discussed in detail. Our investigation exhibits the size controllability of silicon nanocrystals embedded in the silicon nitride film, which implies promising applications in optoelectronic devices such as light-emitting diodes and solar cells.